Laparoscopic cholecystectomy during pregnancy: A systematic review of 590 patients. (March 2016) - Nasioudis, Dimitrios; Tsilimigras, Diamantis; Economopoulos, Konstantinos P.
Abstract: Background: The incidence of symptomatic biliary disease during pregnancy ranges from 0.05 to 8%. Cholecystectomy is one of the common operations performed during pregnancy and laparoscopic approach has gained popularity as an attractive alternative to open surgery. Methods: In order to evaluate the safety, feasibility, outcomes and technical aspects of laparoscopic cholecystectomy during pregnancy a comprehensive search of Medline and Cohrane Library databases was conducted. Results: Fifty-one studies were deemed eligible, in which laparoscopic cholecystectomy was attempted in 590 patients. The majority of the procedures (70.7%) were performed during the second trimester. Intraoperative and postoperative complications were observed in 3.5% and 4% of the study population. Conversion rate to open surgery was 2.2%. Fetal loss rate and preterm delivery rate were 0.4% and 5.7% respectively. Conclusion: Laparoscopic cholecystectomy seems to be a safe alternative to open surgery during pregnancy. Highlights: Laparoscopic cholecystectomy during pregnancy is not associated with significant maternal and fetal morbidity. This procedure should be performed by experienced surgeons in centers with availability of obstetric and neonatal care. There is not enough evidence regarding the preferred modality of cholecystectomy during pregnancy.